IDENTIFIKASI PROTEIN BAKTERI PROBIOTIK ASAL LIMBAH KUBIS DAN SAWI BERDASARKAN ELEKTROFORESIS SDS-PAGE - Wikanastri Hersoelistyorini; Sri Sinto Dewi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Liquid from the fermentation result of cabbage and mustard vegetable-waste is potentiallybecame  probiotic bacterium source. Vegetables and fruits submersion on low or high degree ofsaline (NaCl) will affect the growth of microorganisms from bacteria class that is, LactobacillusPlantarum. Lactobacillus Plantarum is involved in the formation of lactic acid duringfermentation. Leuconostoc, Lactobacillus, and  Pediococcus convert the sugar in the vegetablesinto lactic acid so that limiting the growth of other organisms. The purpose of this research is toidentify probiotic bacterial protein from cabbage and mustard vegetable-waste using SDSPAGEelectrophoresismethodandprobioticbacterialspeciesusingAPI50CHLV5.1method. Theresult of the research is expected in the form of Lactobacillus bacteria can be used as astarter probiotic that has benefit for health. Result reveals that Lactobacillus isolates 3a and 5aare able to grow at low pH (pH 1.5 and 3) and room temperature. The characterization result ofwhole proteins by SDS-PAGE electrophoresis method against two Lactobacillus isolates (3aand 5a isolates), each obtained 13 bands protein. The 13th molecular weight of 3a isolate proteinband, consecutive, as follows: 124.4; 111.6; 102.3; 93.97; 86.2; 79.0; 66.6; 56.1; 43.3; 39.8;36.4; 33.4; and 29.4 kDa. Whereas, the 13th molecular weight of 5a isolate protein band,consecutive, as follows: 121.6; 111.6; 102.3; 86.2; 79.0; 72.6; 66.6; 56.1; 45.2; 39.8; 38.1;34.99; and 29.4 kDa. Based on the identification using API 50 CHL V5.1 medium is known that3a isolate is Lactobacillus Plantarum 1 with %ID reaches 99.5%, while 5a isolate isLactobacillus Plantarum 1 with %ID reaches 99.4%.Kata kunci : API 50 CHL V5.1, cabbage , elektroforesis SDS-PAGE, , Lactobacillus, and mustard vegetable.